PEMIKIRAN ILMU EKONOMI ( ANALISIS KOMPARATIF EKONOMI MASA PRA KLASIK DAN MASA RASULULLAH SAW) - Albanjari, Fatkhur Rahman (LIPI, 2017)
Islam has its own way to run the economy. The Qur'an and Hadith as the ultimate reference for carrying it all, while the pre-classic is merely rationalizing rationality as the development of his scholarship. In this study the author will explore about how the economic system in the Pre-Classical and the Prophet's time. Surely there will be many differences and similarities between the two about the concept of economy. The concept brought by each era has its own development both way, thought and system. The purpose of this paper is to know how the thinking of the classical era economy and the time of the Prophet. The last Islamic economy certainly did not adopt the ideas of its predecessors, but the complement and perfection of the preceding teachings made it more perfect.